Agathis robusta Bark Extract Protects from Renal Ischemia-Reperfusion Injury: Phytochemical, In Silico and In Vivo Studies - Maged E. Mohamed; Nora Tawfeek; Samar S. Elbaramawi; Mahmoud H. Elbatreek; Eman Fikry (MDPI AG, 2022)
Background: Acute kidney injury (AKI) induced by renal ischemia-reperfusion injury (RIRI) is associated with a high incidence of mortality. Existing therapies are mainly supportive, with no available nephroprotective agent. The purpose of this study is to examine the potential protective effect of Agathis robusta Bark Extract (ARBE) in RIRI. Methods: The chemical composition of ARBE was examined by LC-ESI-MS/MS. Network pharmacology was utilized to identify the RIRI molecular targets that could be aimed at by the identified major components of ARBE. Experimentally validated protein-protein interactions (PPIs) and compound-target networks were constructed using the STRING database and Cytoscape software. Molecular docking studies were employed to assess the interaction of the most relevant ARBE compounds with the hub RIRI-related targets. Furthermore, ARBE was tested in a rat model of RIRI. Results: The phytochemical analysis identified 95 components in ARBE, 37 of which were majors. Network analysis identified 312 molecular targets of RIRI that were associated with ARBE major compounds. Of these 312, the top targets in the experimentally validated PPI network were HSP90, EGFR, and P53. The most relevant compounds based on their peak area and network degree value included narcissoside, isorhamnetin-3-O-glucoside, and syringetin-3-O-glucoside, among others. Docking studies of the most relevant compounds revealed significant interactions with the top RIRI-related targets. In the in vivo RIRI experiments, pretreatment of ARBE improved kidney function and structural changes. ARBE reduced the renal expression of p-NfkB and cleaved caspase-3 by downregulating HSP90 and P53 in rats exposed to RIRI. Conclusion: Taken together, this study revealed the chemical composition of ARBE, depicted the interrelationship of the bioactive ingredients of ARBE with the RIRI-related molecular targets, and validated a nephroprotective effect of ARBE in RIRI.